2017
DOI: 10.3758/s13421-017-0781-5
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting having denied: The “amnesic” consequences of denial

Abstract: The concept of denial has its roots in psychoanalysis. Denial has been assumed to be effective in blocking unwanted memories. In two experiments, we report that denial has unique consequences for remembering. In our two experiments, participants viewed a video of a theft, and half of the participants had to deny seeing certain details in the video, whereas the other half had to tell the truth. One day later, all participants were given either a source-monitoring recognition or a recall task. In these tasks, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 37 publications
4
35
1
2
Order By: Relevance
“…What was demonstrated was that participants in the false denial condition exhibited memory impairment for details that they discussed in the first interview. To date, DIF has been replicated in various experiments using different stimuli (i.e., negative and neutral pictures; Otgaar et al, 2016), different memory tasks (recall and recognition; Otgaar et al, 2018), and when participants were instructed to feign memory loss for a crime (Romeo, Otgaar, Smeets, Landström, & Jelicic, 2018).…”
Section: Coping and Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…What was demonstrated was that participants in the false denial condition exhibited memory impairment for details that they discussed in the first interview. To date, DIF has been replicated in various experiments using different stimuli (i.e., negative and neutral pictures; Otgaar et al, 2016), different memory tasks (recall and recognition; Otgaar et al, 2018), and when participants were instructed to feign memory loss for a crime (Romeo, Otgaar, Smeets, Landström, & Jelicic, 2018).…”
Section: Coping and Memorymentioning
confidence: 99%
“…One issue in previous experiments on the effect of denying on memory is that participants were explicitly instructed to falsely deny (e.g., Otgaar et al, 2014; Otgaar et al, 2016; Otgaar et al, 2018; Vieira & Lane, 2013). Of course, in many cases, victims decide themselves whether they will use a certain strategy to cope with an adverse experience.…”
Section: Coping and Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…These deceptive strategies produce different memory outcomes that are also correspondingly placed along a continuum. On the one hand, research has shown that falsely denying certain event‐related details during an interview can eventually lead to forget that those details were previously denied (e.g., Otgaar, Howe, Smeets, & Wang, 2016; Otgaar, Romeo, Howe, & Ramakers, 2018; Polage, 2018). On the other hand, fabricating new information has been shown to increase memory error rates at a later stage (e.g., Van Oorsouw & Giesbrecht, 2008), although it does not seem to undermine the gist of correct recollection (e.g., Ackil & Zaragoza, 2011; Chroback & Zaragoza, 2008).…”
Section: Simulating Amnesia In the Memory And Deception Frameworkmentioning
confidence: 99%
“…In some studies the source of the misinformation that challenges one's original memory comes not from an external source but from oneself, as when one lies about what they experienced. Studies have shown that false denials (e.g., saying “I did not see an orange cat” when in fact I did see an orange cat) can also lead to omission errors in subsequent memory reports (Otgaar & Baker, 2018; Vieira & Lane, 2013; see also Otgaar, Howe, Memon, & Wang, 2014; Otgaar, Romeo, Ramakers, & Howe, 2018). Internal feedback of this sort potentially could lead to the sort of interpersonal dissonance described in our model.…”
Section: Summary and Closing Thoughtsmentioning
confidence: 99%